2017
DOI: 10.1371/journal.pone.0170060
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular exercise and burden of arrhythmia in patients with atrial fibrillation - A randomized controlled trial

Abstract: BackgroundPhysical activity at moderate-high intensity is recommended to prevent lifestyle diseases. Patients with atrial fibrillation are at risk of a sedentary lifestyle due to fear of exercise-induced episodes of atrial fibrillation. The burden of arrhythmia can be reduced by physical exercise. The effect of exercise intensity on burden of atrial fibrillation needs to be studied further.Methods and resultsIn a 12-week randomized controlled trial, 76 patients with paroxysmal/persistent atrial fibrillation we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
66
0
9

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(78 citation statements)
references
References 40 publications
0
66
0
9
Order By: Relevance
“…The Preferred Reporting Items for Systematic Reviews and Meta-Analyses flow diagram (figure 1) describes the selection process. Nine studies (nine publications) were included in this analysis2 10 25–31 (see table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Preferred Reporting Items for Systematic Reviews and Meta-Analyses flow diagram (figure 1) describes the selection process. Nine studies (nine publications) were included in this analysis2 10 25–31 (see table 1).…”
Section: Resultsmentioning
confidence: 99%
“…HRQoL in patients with AF has been shown to be lower than age and sex-matched members of the general population and other cardiac groups, including coronary heart disease (CHD). 9 Beyond medical management, evidence suggests AF may be controlled by improving lifestyle 10 11. One aspect of lifestyle therapy that is poorly understood, with respect to AF, is regular exercise 12…”
Section: Introductionmentioning
confidence: 99%
“…Pathak et al also demonstrated a beneficial effect of aggressive risk factor management on the long-term success of AF ablation (6). Randomized studies on patients with primarily permanent AF have demonstrated beneficial effects of physical exercise on physical capacity, AF symptoms and QoL (7)(8)(9)(10)(11).…”
mentioning
confidence: 99%
“…In a study that examined the effects of the intensity of aerobic exercise on systolic blood pressure both in resting and during the exercise, the results showed that exercise with low and extreme intensity leads to an increase in systolic blood pressure (30). Findings of research on the study of the effects of doing exercise on arterial fibrillation arrhythmia demonstrated that exercise with extreme intensity had no superiority to reduce arterial fibrillation compared to low-intensity exercise (31). Several known mechanisms can be described for blood pressure loss due to exercise.…”
Section: Discussionmentioning
confidence: 99%